(untitled) (Fiep Bulletin - online, 2011)
Cerebral Palsy (CP) is a permanent disorder of posture and movement, caused by a damage in the development of the Central Nervous System (CSN) in the beginning of life. Therefore, this study aims to describe the kinematic characteristics of the gait of a spastic diplegic CP patient and compare them to normal gait patterns found in the literature. For gait kinematic analyze, a tridimensional Digital Motion Analysis System (DMAS) 5.0 was used, where were measured angular variables of hip, knee and ankle articulations. In order to compare the patient gait patterns to the normal gait patterns found in the literature, the Paired t test (p?0,05) was used. Considering the results obtained, the patient analyzed demonstrates crouch gait pattern, with significant decrease in movement amplitude of hip articulation, knee and ankle (p < 0,001), also demonstrates absence of hip hyper-extension and absence of first wave of knee flexion and ankle plantar flexion during gait cycle. Therefore, one believes that the results of this study can contribute in developing rehabilitation programs to help the patient analyzed, focusing on the patient’s principal disabilities. Another similar studies are highly recommended, in order to verify if the findings in the present study also applies to other patients.